Optimizing Sustainable environmental practice in the MSME Sector Through Digitalization, Green Accounting, and Sustainability Awareness with Socioeconomics as a Moderating Variable - Cahyaningtyas, Fadilla; Mulyaningtyas, Mulyaningtyas (PT. EQUATOR SINAR AKADEMIA, 2025)
This study analyzes the influence of digitalization, green accounting, and sustainability awareness on sustainability environmental practice among MSMEs in East Java, with socioeconomic conditions as a moderating variable. Using a mixed-method approach, data were collected through surveys of 207 respondents and semi-structured interviews with 15 informants. The findings reveal that green accounting significantly enhances environmentally friendly practices, while digitalization and sustainability awareness show no direct effect. Furthermore, socioeconomic conditions do not moderate the relationships between the independent variables and environmental practices. These results highlight the persistence of the intention–behaviour gap, as MSMEs often recognize environmental issues but fail to implement systematic green practices due to limited literacy, resources, and external support. The study provides theoretical contributions to the application of the Theory of Planned Behaviour in the MSME context and practical implications for policymakers to strengthen incentives, regulations, and green literacy programs for sustainable MSME development.